The Economic Impacts of Direct Natural Disaster Exposure - Meliyanni Johar; David W. Johnston; Michael A. Shields; Peter Siminski; Olena Stavrunova (Institute of Labor Economics (IZA), 2020)
This paper studies how having your home damaged or destroyed by a natural disaster impacts on economic and financial outcomes. Our context is Australia, where disasters are frequent. Estimates of regression models with individual, area and time fixed-effects, applied to 10 waves of data (2009-2018), indicate that residential destruction has no average impact on employment and income, but increases financial hardship and financial risk aversion. These impacts are generally short-lived, larger for renters than home owners, and greater for smaller isolated disasters. Using a Group Fixed Effects estimator, we find that around 20% of the population have low resilience to financial shocks, and for these individuals we find a substantive increase in financial hardships. The most vulnerable are the young, single parents, those in poor health, those of lower socioeconomic status, and those with little social support. These results can help target government aid after future natural disasters to those with the greatest need.
Keywords: Q54; J21; I31; G50; C23; H84; 330; natural disasters; financial hardship; risk aversion; mental health; resilience